Computer utilization and clinical judgment in psychological assessment reports - Lichtenberger, Elizabeth O. (Journal of clinical psychology, 2006)
The process of assessment report writing is a complex one, involving both the statistical evaluation of data and clinical methods of data interpretation to appropriately answer referral questions. Today, a computer often analyzes data generated in a psychological assessment, at least in part. In this article, the author focuses on the interaction between the decision‐making processes of human clinicians and the test interpretations that are computer‐based. The benefits and problems with computers in assessment are highlighted and are presented alongside the research on the validity of automated assessment, as well as research comparing clinicians and computers in the decision‐making process. The author concludes that clinical judgment and computer‐based test interpretation each have weaknesses. However, by using certain strategies to reduce clinicians' susceptibility to errors in decision making and to ensure that only valid computer‐based test interpretations are used, clinicians can optimize the accuracy of conclusions that they draw in their assessment report © 2005 Wiley Periodicals, Inc. J Clin Psychol.